Answer:
B) y=-3/2x-3
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(-6-3)/(2-(-4))
m=-9/(2+4)
m=-9/6
simplify
m=-3/2
y-y1=m(x-x1)
y-3=-3/2(x-(-4))
y-3=-3/2(x+4)
y=-3/2x-12/2+3
y=-3/2x-6+3
y=-3/2x-3
Answer:
3/4 students (75/100)
Step-by-step explanation:
in total there are 100 students. 75 of them either like sports or works.
Answer:
The answer is 1.
Step-by-step explanation:
Answer:
Step-by-step explanation:
we know that
In the right triangle of the figure XYZ
Applying the Pythagorean Theorem
substitute the given values
square root both sides
Answer:
y=-5x-12
y=-0.5x-5
y=-0.5x+0.5
y=-4.5x+3
y=-2x+7
y=2.5x+10
Step-by-step explanation: